Quinolones antibiotics in the Baiyangdian Lake, China: Occurrence, distribution, predicted no-effect concentrations (PNECs) and ecological risks by three methods. (January 2020) - Zhang, Lulu; Shen, Lina; Qin, Shan; Cui, Jiansheng; Liu, Yong
Abstract: The occurrence, distribution, and ecological risk of 10 quinolones (QNs) were investigated in the water and sediment samples from Baiyangdian Lake, China. The field samplings were conducted in April (dry season) and August (wet season) 2018, the results showed that QNs was extensively distributed in the Baiyangdian Lake. For the occurrence, Flumequine (FLU) and Ofloxacin (OFL) were the most detected QNs in Baiyangdian Lake. For the temporal variation, the sum concentration of QNs in water and sediment were ranged from 153 ng/L to 3093 ng/L and from 40.1 ng/g to 1475 ng/g in April, while ranged from 3.83 ng/L to 769 ng/L and from 20.3 ng/g to 373 ng/g in August. For the spatial variation, all of QNs exhibited significance difference in concentration at different sampling areas. Furthermore, PNEC plays an important role in ecological risk assessment, thus the PNECs of FLU and OFL were derived by assessment factors (AF), species sensitivity distribution (SSD), and AQUATOX model methods. The results showed that: PNECAFs, PNECSSDs, and PNECAQUATOXs were 18.7 μg/L, 196 μg/L, and 128 μg/L for FLU, respectively; and were 0.021 μg/L, 4.40 μg/L, and 3.00 μg/L for OFL, respectively. The PNECs for FLU and OFL derived by three approaches showed the rank of: PNECSSDs > PNECAQUATOXs > PNECAFs ; while the risk quotients (RQs) followed the other rank of: RQSSDs < RQAQUATOXs < RQAFs . The results was indicated that the indirect ecological effects plays an important role in the derived PNECs for QNs, without considering the indirect ecological effects in natural ecosystem can lead to under-protective or over-protective PNECs (RQs) for chemicals. Therefore, AQUATOX model can be applied in deriving PNECs during the ecological risk assessment. Graphical abstract: Fig. 1 The conceptual figure for migration and transformation of antibiotics in Lake. Image 1 Highlights: The occurrence and distribution of QNs was investigated in Baiyangdian Lake. Ofloxacin and Flumequine were the dominant QNs in Baiyangdian Lake. PNECs and ERAs of QNs were assessed by AF, SSD, and AQUATOX methods. AQUATOX model can be applied in deriving more reasonable PNECs. Abstract : Apply AF, SSD, and AQUATOX model methods to assess the PNEC and ecological risk of QNs in Baiyangdian Lake.